Multiple endocrine neoplasia type 2‐like syndrome in a crossbred dog. Issue 2 (5th April 2021) - Cervone, Mario; Blondel, Margaux; Moissonnier, Pierre; Chabanne, Luc
Abstract: A 9‐year‐old spayed female crossbred dog was referred with a 6‐month history of polyuria/polydipsia associated with systemic arterial hypertension and hypokalaemia according to clinical and biochemical evaluations, respectively. Pheochromocytoma with concomitant unilateral nonsecreting thyroid carcinoma and ipsilateral nonsecreting parathyroid hyperplasia were diagnosed by ultrasonography, computed tomography, cytology and histopathology. Surgical treatment allowed for the complete resolution of clinical and biochemical abnormalities, and no recurrence was found during the one‐year clinical follow‐up. To the best of the author's knowledge, this is the third report describing multiple endocrine neoplasia type 2‐like syndrome in dogs, and it further characterizes this rare condition.